1987
DOI: 10.1590/s0074-02761987000400013
|View full text |Cite
|
Sign up to set email alerts
|

Influence de l'anhydrobiose sur l'infestation de Biomphalaria glabrata par un miracidium de Schistosoma mansoni

Abstract: 410 Biomphalaria glabrata (Caribbean strain of Guadeloupe) have been infected with one miracidium of Schistosoma mansoni, 110 snails, used as controls have been kept into water; the survival rate was 96.4% after 4 weeks and 25.4% produced cercariae. 300 snails were kept on wet soil, and submitted for 6 weeks to progressive desiccation. The survival rate was 23.4% but only 9 of them produced cercariae. Periodic variations of the production of male and female larvae have been shown by the weekly test of the cerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The desiccation, in spite of not having impeded, probably caused a pause in the development of the sporocysts I found in group V. The sporocysts I, of the group V and of the 7 days control group, were located in the anterior area of the mollusks. Experiments with desiccation in mollusks of B. glabrata, containing larvae of sporocyst I in the initial stage and of sporocyst I showing in their interior sporocysts II in formation, were accomplished by Barbosa and Coelho (1955) and Lancastre et al (1987). Theses authors also observed a pause in the development of the larvae.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The desiccation, in spite of not having impeded, probably caused a pause in the development of the sporocysts I found in group V. The sporocysts I, of the group V and of the 7 days control group, were located in the anterior area of the mollusks. Experiments with desiccation in mollusks of B. glabrata, containing larvae of sporocyst I in the initial stage and of sporocyst I showing in their interior sporocysts II in formation, were accomplished by Barbosa and Coelho (1955) and Lancastre et al (1987). Theses authors also observed a pause in the development of the larvae.…”
Section: Discussionmentioning
confidence: 98%
“…Studies on the resistance to desiccation were accomplished with B. glabrata, B. straminea and B. pfeifferi by Barbosa and Dobbin (1952), Olivier andBarbosa (1955, 1956), Olivier (1956), JongBrink (1973), Pieri et al (1980), Vianey-Liaud and Lancastre (1986) and Vianey-Liaud and Dussart (1994) with healthy mollusks, and by Barbosa (1953), Barbosa andCoelho (1953, 1955), Barbosa and Barbosa (1958), Lancastre et al (1987Lancastre et al ( , 1989 and Badger and Oyerinde (1996) with mollusks infected by S. mansoni. Only one study on the resistance of B. tenagophila to desiccation is known.…”
mentioning
confidence: 99%
“…Studies on the resistance to desiccation were carried out on healthy specimens of B. glabrata, B. straminea and B. pfeifferi by BARBOSA & DOBBIN (1952) 7 , OLIVIER & BARBOSA (1955,1956) 24,25 , PIERI et al (1980) 38 , VIANEY-LIAUD & LANCASTRE (1986 a and b) 50,51 , VIANEY-LIAUD & DUSSART (1994) 52 and JONG-BRINK (1973) 20 . These studies were also carried out on mollusks infected by S. mansoni by BARBOSA (1953, 1959) 2,3 , BARBOSA & COELHO (1953,1955) 5,6 , BARBOSA & BARBOSA (1958) 4 , LANCASTRE et al (1987,1989) 22,23 and BADGER & OYERINDE (1996) 1 . For B. tenagophila, only TELES & MARQUES (1989) 49 , are cited.…”
Section: Introductionmentioning
confidence: 99%